Microfluidic chip for blood sample processing - Chalapathy Raja Shobana (2018)
Blood is perhaps the most important window through which person’s illness and health are determined. The results of these tests will trigger further testing. In under-developed countries, detection of disease and treatment at an early stage are unlikely causing the severity of disease more rapid. To make it simpler, the Paper-based microfluidic chip is developed from the conventional blood sample processing that provides timely diagnosis by conducting tests instantly at home care. It requires only a tiny amount of blood sample i.e., in μL for analysis. Hence, in this study, a novel and superficial method have been put forward with the 3D origami paper-based analytical devices in the diagnosis of malaria using SERS measurement. 3D origami paper device (paper folding) are fabricated from cellulose paper with millimeter dimensions, paper acting as a natural platform for microfluidics by Xia, et al., [1]. The blood sample is drawn from the top layer to subsequent layers below by gravitational force action. The aluminum coating on the surface of filter paper traps the parasites, which is later observed under Raman Spectroscopy for detection of disease. Paper is particularly suitable for SERS studies as it will not interfere with the Raman signal of the analyte. The coating done will be best suited for biological and analytical applications such as SERS. As new trends are emerging in diagnostics, this method commercially attracts the use of paper-based devices at healthcare.